Impacts Sociaux Et Environnementaux De L’orpaillage Sur Les Populations De La Region Du Bounkani (Cote D’ivoire) - AFFESSI Adon Simon; KOFFI Koffi Gnamien Jean-Claude; SANGARE Moussa (European Scientific Journal, ESJ, 2016)
This work highlights the effects of the practice of rural panning. This activity is considered a factor in promoting better condition of life of the miners. Its implementation modifies the relations of individuals with nature. The action of the miners, in their quest for wellness, causes social, economic and relationship with adverse environmental consequences. The study method was to collect information from resource persons and the use of functionalist theories and structural-functionalist. The results indicate that gold mining activity, although revenue generating negatively affect the environment, food safety and the health of populations in the Region Bounkani.